2018
DOI: 10.1002/jcb.26670
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression profile of long non‐coding RNAs in human thoracic aortic aneurysm

Abstract: Thoracic aortic aneurysm (TAA) is progressive fatal aortic pathological dilation, which is characterized by increased proteoglycans and loss of elastic fibers. Recent advances in long non-coding RNAs (lncRNAs), an important regulator in many biological processes, suggested the close correlation between expression patterns and disease progression. In the present study, the ascending aortic tissues were collected from ascending TAA patients (n = 33) and organ donors (n = 16). Microarray analysis and real-time PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…LncRNA-related VSMC dysfunction and ECM degradation were suggested as potential mechanisms according to recent data. Microarray profile analysis revealed that hundreds and thousands of lncRNAs are involved in human thoracic aortic aneurysm (TAA) development, such as Lnc-HLTF-5 [44], HIF1A-AS1, RP11-465L10.10, and CTD-2184D3.5 [45], which might play roles in regulating the expression of MMP-9 in aortic tissue and then facilitate the expansionary remodeling. HIF1alpha-antisense RNA 1 (HIF1A-AS1) was the first reported lncRNA participating in TAA pathogenesis [46].…”
Section: The Regulatory Role Of Lncrna In Cardiac Remodelingmentioning
confidence: 99%
“…LncRNA-related VSMC dysfunction and ECM degradation were suggested as potential mechanisms according to recent data. Microarray profile analysis revealed that hundreds and thousands of lncRNAs are involved in human thoracic aortic aneurysm (TAA) development, such as Lnc-HLTF-5 [44], HIF1A-AS1, RP11-465L10.10, and CTD-2184D3.5 [45], which might play roles in regulating the expression of MMP-9 in aortic tissue and then facilitate the expansionary remodeling. HIF1alpha-antisense RNA 1 (HIF1A-AS1) was the first reported lncRNA participating in TAA pathogenesis [46].…”
Section: The Regulatory Role Of Lncrna In Cardiac Remodelingmentioning
confidence: 99%
“…An increasing number of studies have demonstrated the direct role of lncRNAs in the pathogenesis of various human diseases including tumors, inflammatory, cardiovascular, and immunological diseases [ 3 , 5 ]. In many studies, the regulatory mechanism of lncRNAs in aortic aneurysms was also shown, which was directly associated with the formation, growth and dissection of the aorta ( Table 1 ) [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In recent years, increasing studies have focused on role lncRNAs in the pathogenesis of IAs.…”
Section: Lncrnas and Iasmentioning
confidence: 99%
“…So far, H19 is the only lncRNA found to be involved in AAA formation (71). Although involvement in vascular disease has been demonstrated for a number of other lncRNAs (5,70,73), distinctive functional roles in AAA formation have not been proven. Knockdown of H19 using antisense oligonucleotides led to a significant reduction of aneurysm formation in two different murine AAA models.…”
Section: Long Noncoding Rnamentioning
confidence: 99%